The Use of Taro as A Potato Substitute and The Addition of Aglio Olio Sauce in The Manufacture of Gnocchi - Fatimah Nur Azzahra; Riza Taufiq (Publikasi Indonesia, 2024)
This research aims to explore the utilization of taro as a substitute for potatoes in making gnocchi and the addition of aglio olio sauce to enhance taste and texture. The research findings indicate that taro can be used as a substitute for potatoes with a relatively high level of acceptability. The addition of aglio olio sauce also enhances the overall taste and aroma of gnocchi. This research contributes to the development of innovative and sustainable food products, offering a new perspective on the utilization of lesser-used plants in the culinary industry. This research is an experimental study. Taro was chosen as the raw material because, although it has many benefits and is underutilized, it has a high nutritional value. The organoleptic test of the taro utilization as a substitute for potatoes and the addition of aglio olio sauce in the production of gnocchi was conducted using a Likert scale from 1 to 5, with higher values indicating better quality. The panel consisted of 20 members of the public, with an equal number of men and women and an average age of 30 years. They were randomly selected and had no special skills in the culinary field. The product received good ratings in terms of sensory taste, such as spicy, sweet, sour, savory, and general. The findings of this study are that the optimal process of utilizing taro as a substitute for potatoes and adding aglio olio sauce in the production of gnocchi requires a series of meticulous and efficient steps. From the soaking and cleaning stages to the serving stage, each step must be carefully executed to ensure the quality of the final product.